EFEKTIVITAS BELANJA DESA DALAM MENURUNKAN KEMISKINAN DI KABUPATEN BANDUNG BARAT - Hasibuan, Sarah; Yamin, Fauji (LPPM Universitas Terbuka, 2024)
The Village Fund as fulfillment of the village's right in implementing regional autonomy so that the village can grow and develop based on its potential. The poverty study aims to analyze the effect of village spending (village spending on village governance, village infrastructure development, empowerment and development of village communities) on poverty. This study uses cross-sectional data from 165 villages, with a Geographically Weighted Regression (GWR) model. This study uses cross-sectional data from 165 villages, with a Geographically Weighted Regression (GWR) model. The results of the GWR analysis show that village spending in the field of government administration has no effect on poverty. Village expenditures for physical infrastructure development, community empowerment and development have an effect on reducing poverty.